Effect of Glass Composition on Luminescence and Structure of CsPbBr3 Quantum Dots in an Amorphous Matrix - Zheng, Ruilin; Ueda, Jumpei; Shinozaki, Kenji; Tanabe, Setsuhisa (Materials, 2022)
Glass matrix embedding is an efficient way to improve the chemical and thermal stability of the halide perovskite QDs. However, CsPbX3 QDs exhibit distinct optical properties in different glass matrixes, including photoluminescence (PL) peak position, PL peak width, and optical band gap. In this work, the temperature-dependent PL spectra, absorption spectra, high-energy X-ray structure factor S(Q), and pair distribution function (PDF) were integrated to analyze the structural evolution of CsPbBr3 QDs in different glass matrixes. The results show that the lattice parameters and atomic spacing of CsPbBr3 QDs are affected by the glass composition in which they are embedded. The most possibility can be attributed to the thermal expansion mismatch between CsPbBr3 QDs and the glass matrix. The results may provide a new way to understand the effect of the glass composition on the optical properties of CsPbBr3 QDs in a glass matrix.